1995
DOI: 10.1002/chir.530070813
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of a single intravenous dose of rac‐propranolol versus optically pure propranolol in the rat

Abstract: Conscious male Wistar SPF Riv:TOX rats were dosed intravenously with 2.5, 5, or 10 mg/kg rac-propranolol.HCl, or with 5 mg/kg of either (-)-(S)- or (+)-(R)-propranolol.HCl. Disposition of (-)-(S)- and (+)-(R)-propranolol after dosing of rac-propranolol was linear in the dose range examined. Total plasma clearance was not changed in animals dosed with the individual enantiomers compared to the animals that were dosed with rac-propranolol. However, for (-)-(S)-propranolol both volume of distribution and eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Enantiomeric interactions (Zhou et al 2002) have been reported for D-cefalexin (Tamai et al 1988) during the absorption phase, propranolol (Bode et al 1995) and disopyramide (Takahashi et al 1991) during the distribution phase, cisapride (Desta et al 2001), propafenone (Li et al 1998) and nitrendipine (Tokuma & Noguchi 1995) during the metabolic phase and sotalol (Carr et al 1994) during the excretion phase. As far as the 2-arylpropionic acids (2-APAs) of NSAIDs are concerned, an enantiomer± enantiomer interaction after intravenous administration of flurbiprofen has been demonstrated following displacement from plasma protein binding sites (Berry & Jamali 1989), but there was no evidence of a pharmacokinetic interaction between the enantiomers of etodolac (Brooks & Jamali 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Enantiomeric interactions (Zhou et al 2002) have been reported for D-cefalexin (Tamai et al 1988) during the absorption phase, propranolol (Bode et al 1995) and disopyramide (Takahashi et al 1991) during the distribution phase, cisapride (Desta et al 2001), propafenone (Li et al 1998) and nitrendipine (Tokuma & Noguchi 1995) during the metabolic phase and sotalol (Carr et al 1994) during the excretion phase. As far as the 2-arylpropionic acids (2-APAs) of NSAIDs are concerned, an enantiomer± enantiomer interaction after intravenous administration of flurbiprofen has been demonstrated following displacement from plasma protein binding sites (Berry & Jamali 1989), but there was no evidence of a pharmacokinetic interaction between the enantiomers of etodolac (Brooks & Jamali 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Their metabolisms have stereoselective differences . Animal experiments show that the S‐type enantiomer beta‐blockade is about 100 times stronger than the R‐type and has a longer half‐life in the blood . Meanwhile, R‐propranolol can inhibit sexual desire and is a male contraceptive .…”
Section: Quantification Of Propranolol Enantiomers By Mass Spectrometmentioning
confidence: 99%
“…Sometimes, racemic betablockers are toxic showing some serious side effects. For example racemic propranolol is more toxic than its individual enantiomers in rat [39].…”
Section: Introductionmentioning
confidence: 99%
“…It is also clear from that S-propranolol is capable of providing strong bonding to receptor in comparison to R-enantiomer, and that is why Senantiomer is more pharmacologically active. Besides, other forces such as van der Waals, dipole induced dipole and steric may contribute for the binding of beta-blockers on beta-receptor site [39,40]. …”
Section: Introductionmentioning
confidence: 99%